PENGARUH MODEL PEMBELAJARAN IMPROVE DENGAN METODE ACCELERATED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA - DEWI, RATNA; SUKASNO, SUKASNO; ELLY, AS (Universitas Muhammadiyah Bengkulu, 2019)
This research was took based on the low ability of understanding about the concept of mathematics by students. The objective at this research was there were any impact teaching model IMPROVE with Accelerated Learning Method toward students’ ability in understanding the concept of mathematics at grade VIII MTs Negeri 1 Lubuklinggau in academic years 2019/2020. The method at this research was True Eksperimental Design. The population was all students grade VII that consist of 288 students and the sample as exsperimental class VIII.1 and as the class control was VIII.3. In collecting the data the researcher used test. The data that was collected, it was analysed by t-test. The result showed that level of sicnificances = 0,05, it can be concluded that there were impact teaching model IMPROVE with Accelerated Learning Method toward students’ ability in understanding the concept of mathematics at grade VIII MTs Negeri 1 Lubuklinggau in academic yeas 2019/2020. The avarage of students’ score in understanding the concept of mathematics after giving threatment in the class experiment were 56.40 and control class was 40,90.